Agency Control on Capital Market Efficiency: Evidence from Earnings Announcement - Peranginangin, Adat Muli (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
This study investigates how agency control influences the market's response to new information disclosed during earnings announcements. The aim is to investigate the potential connection between agency control and market efficiency. The research employs an event study as the principal metric and ordinary least squares to evaluate the relationship between agency control and the firms' cumulative earnings announcement returns. This study analyzes the effect of earnings announcements on abnormal returns, utilizing 93,244 daily data from all listed firms between July 2018 and December 2019, specifically during the reporting of year-end financial statements as of December 31, 2018. The study reveals that firms under concentrated ownership and family control do not conform to the semi-strong form of market efficiency, as evidenced by the absence of significant abnormal returns during the event. Insignificant abnormal returns following earnings announcements indicate that the market has assimilated the firms' financial information before the announcement date, as these stakeholders possess privileged access to the firms' information well in advance of the announcements. As a result, the market no longer receives new information from the event or encounters any significant unforeseen news. Consequently, the study determines that agency control may affect the market efficiency of a capital market. The study advises policymakers to examine this issue and adopt measures to alleviate information asymmetry between controlling and non-controlling shareholders.